Gestational Diabetes Mellitus: The Genetic Susceptibility Behind the Disease - Wei, Wenwen; He, Yuejuan; Wang, Xin; Tan, Guiqin; Zhou, Fangyu; Zheng, Guangbing; Tian, Dan; Ma, Xiaomin; Yu, Hongsong (Hormone and Metabolic Research, 2021)
Gestational diabetes mellitus (GDM), a type of pregnancy-specific glucose intolerance or hyperglycemia, is one of the most common metabolic disorders in pregnant women with 16.9% of the global prevalence of gestational hyperglycemia. Not only are women with GDM likely to develop T2DM, but their children are also at risk for birth complications or metabolic disease in adulthood. Therefore, identifying the potential risk factors for GDM is very important in the prevention and treatment of GDM. Previous studies have shown that genetic predisposition is an essential component in the occurrence of GDM. In this narrative review, we describe the role of polymorphisms in different functional genes associated with increased risk for GDM, and available evidence on genetic factors in the risk of GDM is summarized and discussed.
Keywords: gestational diabetes mellitus, single-nucleotide polymorphism; genetics; susceptibility